Conflicts in international environmental law - Wolfrum, Rüdiger (Beiträge zum ausländischen öffentlichen Recht und Völkerrecht, 2003)
This volume is an important contribution to both theoretical and practical approaches to solving contradictions and conflicts between the approaches, principles, objectives and regulations of international environmental agreements. The issue of the coordination and streamlining of environmental agreements is of growing importance regarding the increasing number of international regulations on the one hand and the urgency for effective instruments in the light of continuing environmental degradation on the other. This study will become an essential reference for scholars as well as practitioners working in the field of international environmental law.
Keywords: Internationales Umweltrecht